Indescribable - Giglio, Louie; Passion Conferences (Roswell, Ga. : Passion Conferences, 2005)
Video that takes us on an image-rich journey through the Cosmos, allowing us to peer into God's universe to discover the amazing magnitude of His greatness and grace.
Part 1 : Significant insignificance -- Part 2 : Astronomical grace.
Title from container.
Multi-angle setup (select the angle of the talk you want to watch).
"A 2-part DVD video series."-Container.
DVD. Dolby digital.
Keywords: Astronomy -- Religious aspects -- Christianity; Glory of God; God -- Attributes; Creation